Front Cover: Data‐Independent Acquisition‐Based Quantitative Proteomics Analysis Reveals Dynamic Network Profiles during the Macrophage Inflammatory Response. Issue 2 (16th January 2020) - Li, Lei; Chen, Li; Lu, Xinya; Huang, Chenyang; Luo, Haihua; Jin, Jingmiao; Mei, Zhuzhong; Liu, Jinghua; Liu, Cuiting; Shi, Junmin; Chen, Peng; Jiang, Yong
Abstract : DOI: 10.1002/pmic.201900203 In article number 1900203, Lei Li et al. reveal discrete modules and the signaling network that modulates the development of inflammation. The cover depicts the workflow for DIA‐based quantitative proteomics analysis on the inflammatory response of macrophages challenged with LPS. a) Quality analysis of raw data for quantitative proteomics; b) Analysis on protein expression patterns; c) Sequential analysis of differential expression proteins; d) KEGG pathway analysis with ClueGO of the Cytoscape software; e) Integrated analysis of transcriptomics and proteomics.